A Semantic Analysis of Denotative and Connotative Meaning in the Song Lyrics "Anti Hero" by Taylor Swift - Selina Grace Kaizura Simbolon; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the denotative and connotative meanings in the song lyrics “Anti-Hero” by Taylor Swift. The research applies a qualitative descriptive method, focusing on semantic analysis to interpret the meanings conveyed in the lyrics. The data are collected from the official song lyrics and analyzed based on the theory of meaning proposed by Geoffrey Leech, particularly the distinction between denotative (literal) and connotative (associative) meanings. The findings reveal that the denotative meanings in the song are generally straightforward and reflect the literal interpretation of the words. However, the connotative meanings expose deeper emotional and psychological themes, including self-criticism, insecurity, anxiety, and inner conflict. The lyrics demonstrate how simple expressions can carry complex implied meanings through figurative language and personal reflection. In conclusion, the study shows that connotative meaning plays a dominant role in conveying the overall message of the song. The use of semantic analysis helps uncover the hidden meanings behind the lyrics and provides a deeper understanding of the artist’s expression. This study contributes to the field of Semantics by illustrating how meaning is constructed and interpreted in contemporary song lyrics.